Early Clinical Outcomes of Intra‐Articular Injections of Bone Marrow Aspirate Concentrate for the Treatment of Early Osteoarthritis of the Hip and Knee: A Cohort Study. Issue 12 (1st December 2018) - Rodriguez‐Fontan, Francisco; Piuzzi, Nicolas S.; Kraeutler, Matthew J.; Pascual‐Garrido, Cecilia
Abstract: Background: Bone marrow aspirate concentrate (BMC) is one of the few cell‐based therapies available as a possible biological treatment for early osteoarthritis (OA). Its efficacy, safety, and benefit compared with other treatments are still to be determined. Objective: To assess the clinical outcomes of patients undergoing intra‐articular injection of BMC for the treatment of early knee and hip OA. Design: Prospective, cohort study. Setting: Single institution, quaternary level of care. Patients: Nineteen patients (16 female and 3 male), totaling 25 joints (10 knees, 15 hips), treated with intra‐articular BMC for early OA between 2014 and 2016. The mean age at time of the procedure was 58 ± 12.7 years (range, 30‐80 years). The mean follow‐up was 13.2 ± 6.3 months (range, 6‐24 months). Inclusion criteria included ≥18 years; knee OA, Kellgren–Lawrence grade I‐II; hip OA, Tönnis grade I‐II; first‐time intra‐articular BMC therapy, after unsuccessful symptomatic and conservative treatments (ie, physical therapy, analgesics and anti‐inflammatory drugs) for 6 months. Exclusion criteria included pregnancy; malignancy; rheumatologic diseases; infection; Kellgren–Lawrence grade III‐IV; Tönnis grade III; and previous intra‐articular injections or surgery. Interventions: All patients had autologous bone marrow aspirate harvested from the iliac crest and centrifuged to achieve BMC, for intra‐articular injection. Main Outcome Measurements: The hypothesis was formulated before the study. Patient‐reported outcomes measures were assessed preoperatively and at last follow‐up using the Western Ontario and McMaster Universities Arthritis Index. Results: Western Ontario and McMaster Universities Arthritis Index improved from a baseline of 40.8 ± 18.3% to 20.6 ± 17% ( P  < .001) at final follow‐up. The satisfaction rate was 63.2%. The minimal clinically important difference threshold of 9.15 points was reached by 64% of the patients. Two patients were converted to total hip arthroplasty at 8 months after BMC injection. Conclusions: Intra‐articular injections of BMC for the treatment of early knee or hip OA were safe and demonstrated satisfactory results in 63.2% of patients. Future studies are necessary to determine the efficacy of this technique and its safety profile. Level of Evidence: II